Implementación y desarrollo de prácticas de automatización a través de un módulo didáctico con el PLC S7-1200 para el control de intercambiador de calor - Triana Andrade, Marco Gabriel (2017)
This research project will be carried out taking into account the basic needs of students in the vocational training process, taking into account that the heat exchanger is an essential part of refrigeration, air conditioning and energy production systems. Purpose is to provide a tool capable of operating under an automated engineering environment that will allow real simulations in equipment used in automation, particularly in control systems, it is important to note that the main objective of the research is to implement a digital didactic module with the PLC Simatic S7-1200 to demonstrate a heat exchanger. PLCs are widely used today in the educational and business fields, so it is proposed to make the didactic module to be able to perform real practices of the different industrial processes, the project has the following methodological characteristics, bibliographic research because it requires the argument of several authors the same ones that are detailed in the references. The data collection will be used the same technique of the survey that will be tabulated to determine the needs and requirements of the respondents, in addition this type of research will contribute to familiarize us with the problem, the research is field allowing the students to perform different practices enriching their knowledge to perform in the best way in the workplace.